POLA KOMUNIKASI KEPEMIMPINAN DALAM MEMOTIVASI KARYAWAN MELALUI PROGRAM SPIRITUAL BUILDING DI AQIQAH AL-KAUTSAR YOGYAKARTA - Eko Wicaksono, Mahmud Arief; Sa'idah, Zahrotus (Fakultas Dakwah Institut Dirosat Islamiyah Al-Amien Prenduan, 2025)
This study aims to examine leadership communication patterns in motivating employees through the Spiritual Building program at Aqiqah Al-Kautsar Yogyakarta, an Islamic value based service organization. This phenomenon arises from the need of religious institutions to foster work motivation that is not only professional but also spiritual. The research employs a qualitative approach with a case study method, allowing for an in-depth exploration of communication practices within social and religious contexts. Data were collected through semi-structured interviews with leaders and employees, participatory observations of Spiritual Building activities, and analysis of internal documentation. The findings reveal three main themes: (1) a leadership communication style that is assertive, reflective, and humanistic; (2) the integration of Islamic values into daily communication; and (3) the significant impact of spiritual communication on employee motivation and work behavior. Leadership communication functions not only as a means of delivering instructions but also as a medium for internalizing religious values, strengthening loyalty, and cultivating a transcendent sense of work. These findings broaden the understanding of spiritual leadership in Islamic service organizations and highlight the strategic role of communication in fostering a religious work culture. The implications of this study are relevant to the development of value-based leadership theories and managerial practices in religious organizations. Future research is recommended to use a comparative design to assess the sustainability of spiritual communication’s impact in similar institutions.